Meningkatkan Kesejahteraan Masyarakat melalui Pelatihan Sport Massage di Kota Samarinda - Muchamad Samsul Huda; Didik Cahyono; Muhammad Sukron Fauzi; Gyta Krisdiana Cahyaningrum; Naheria Naheria; Muhammad Saiin (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
The community service program titled "Improving Welfare through Sport Massage Training in Samarinda City" aimed to equip participants with sport massage skills beneficial for health and economic potential. The program was conducted through a comprehensive approach, including material delivery, treatment demonstrations, hands-on practice, skill evaluation, and real-condition simulations. The initial stage focused on delivering basic concepts of sport massage, simple anatomy and physiology, and fundamental techniques through interactive presentations. Experienced instructors then demonstrated proper massage techniques on main body parts and specific areas prone to tension or injury, emphasizing safety and comfort. Participants were divided into small groups for hands-on practice, receiving guidance and feedback from instructors. Skill evaluation ensured participants understood correct and safe techniques. Real-condition simulations allowed participants to role-play as massage service providers, enhancing their confidence in handling clients professionally. The program resulted in high participant satisfaction levels, with the highest satisfaction in the practice and simulation sessions. Participants showed significant improvement in understanding and applying sport massage techniques, and increased readiness to practice their skills professionally. This community service program successfully empowered participants with valuable skills that contribute to both health and economic well-being in Samarinda City.